Treatment of hilar cholangiocarcinoma of Bismuth-Corlette type III with hepaticojejunostomy - Lu, Bao-Chun; Ren, Pei-Tu (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study : The present study aims to explore the value of application of hepaticojejunostomy in surgical treatment of Bismuth-Corlette type III hepatic hilar cholangiocarcinoma. Material and methods : The clinical data of hepaticojejunostomy in 6 patients with Bismuth-Corlette type III hepatic hilar cholangiocarcinoma from January 2008 to October 2011 were retrospectively analyzed. There were 5 males and 1 female, aged 45–69 years, on average 58 years old. There were 3 cases of Bismuth-Corlette type IIIa and 3 cases of Bismuth-Corlette type IIIb. Results: The 6 patients all successfully underwent hepaticojejunostomy, with operation time of 160–310 min, on average 210 ±28 min. One patient suffered a small amount of bile leakage (3–20 ml) and his drainage tube was taken out after being cured with conservative treatment for 18 days. Three patients showed postoperative mild increases of aspartate aminotransaminase (AST), alanine transaminase (ALT) and AKP, which were improved after drug treatments. There was no biliary stricture in the 6 patients after follow-up for 3–18 months. Conclusions : Hepaticojejunostomy was simple and flexible, with a good effect on biliary reconstruction of Bismuth-Corlette type III hepatic hilar cholangiocarcinoma. It solved the difficulties in multiple choledochojejunostomy, and with less complications; therefore, it is worth being popularized.